New Subclasses of Multivalent Analytic Functions Associated with a Linear Operator - Ding-Gong Yang; Jin-Lin Liu (Abstract and Applied Analysis)
Making use of a linear operator, which is defined here by means of the Hadamard product (or convolution), we consider two subclasses and of multivalent analytic functions with negative coefficients in the open unit disk. Some modified Hadamard products, integral transforms, and the partial sums of functions belonging to these classes are studied.